2010
DOI: 10.1126/science.1193697
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Partitioning of P Granule Components Is Not Required to Specify the Germline in C. elegans

Abstract: SUMMARY Asymmetric segregation of P granules during the first four divisions of the C. elegans embryo is a classic example of cytoplasmic partitioning of germline determinants. It is thought that asymmetric partitioning of P granule components during mitosis is essential to distinguish germline from soma. We have identified a mutant (pptr-1) where P granules become unstable during mitosis and P granule proteins and RNAs are distributed equally to somatic and germline blastomeres. Despite symmetric partitioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
169
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(180 citation statements)
references
References 21 publications
10
169
0
1
Order By: Relevance
“…P granules are implicated in germ-line establishment and maintenance, but their precise function remains largely unknown. A recent study has shown that segregation of P granules to progenitor germ cells is only necessary for germ-line specification under certain conditions, suggesting a potential role for P granules in protection from stress (34); consistent with this, recent work has implicated LAF-1 and its close homolog VBH-1 in the stress response of C. elegans (35). P granules likely function in cytoplasmic RNA regulation, including storage and release of mRNA transcripts (36,37).…”
Section: Discussionmentioning
confidence: 57%
“…P granules are implicated in germ-line establishment and maintenance, but their precise function remains largely unknown. A recent study has shown that segregation of P granules to progenitor germ cells is only necessary for germ-line specification under certain conditions, suggesting a potential role for P granules in protection from stress (34); consistent with this, recent work has implicated LAF-1 and its close homolog VBH-1 in the stress response of C. elegans (35). P granules likely function in cytoplasmic RNA regulation, including storage and release of mRNA transcripts (36,37).…”
Section: Discussionmentioning
confidence: 57%
“…These were labeled with a GFP-PGL-1 fluorescent fusion protein (Gallo et al, 2010). Images were acquired in 3D at 10-second intervals from metaphase until the one-cell embryo had divided.…”
Section: Chromatin Rotates Around the Anterior-posterior Axis During mentioning
confidence: 99%
“…For example, P-granules are transported along the cytoplasm (8), but it was demonstrated that the flow does not contribute to asymmetric localization of P-granules (11). Cytoplasmic flow might be important for the asymmetric localization of other components that localize posteriorly at this stage, or may stimulate association of cytoplasmic material with the posterior cortex (8,12).…”
mentioning
confidence: 99%